# For n consider integral sign (upper limit3-lower limit 2) x^n/(x^2-1)dx. Show the In+2-In=3^(n+1)-2^(n+1)/n+1

### 1 Answer | Add Yours

You need to consider that `I_n = int_2^3 (x^n)/(x^2-1) dx` , hence, you may write `I_(n+2)` such that:

`I_(n+2) = int_2^3 (x^(n+2))/(x^2-1) dx`

You need to evaluate `I_(n+2) - I_n` such that:

`I_(n+2) - I_n = int_2^3 (x^(n+2))/(x^2-1) dx - int_2^3 (x^n)/(x^2-1) dx`

`I_(n+2) - I_n = int_2^3 (x^(n+2) - x^n)/(x^2-1) dx`

Notice that `x^(n+2) = x^n*x^2` , hence, you may factor out x^n such that:

`I_(n+2) - I_n = int_2^3 x^n*(x^2 - 1)/(x^2-1) dx`

Reducing by `x^2 - 1` yields:

`I_(n+2) - I_n = int_2^3 x^n dx`

`I_(n+2) - I_n = (x^(n+1))/(n+1)|_2^3`

You need to remember that `int_a^b f(x)= F(b) - F(a).`

`I_(n+2) - I_n = 3^(n+1)/(n+1)- 2^(n+1)/(n+1) `

`I_(n+2) - I_n = (3^(n+1)- 2^(n+1))/(n+1) `

**Hence, evaluating the given difference yields that `I_(n+2) - I_n = (3^(n+1)- 2^(n+1))/(n+1) .` **